Estimates for the Green function and singular solutions for polyharmonic nonlinear equation - Imed Bachar; Habib Màagli; Syrine Masmoudi; Malek Zribi (Abstract and Applied Analysis)
We establish a new form of the 3G theorem for polyharmonic Green function on the unit ball of ℝn(n≥2) corresponding to zero Dirichlet boundary conditions. This enables us to introduce a new class of functions Km,n containing properly the classical Kato class Kn. We exploit properties of functions belonging to Km,n to prove an infinite existence result of singular positive solutions for nonlinear elliptic equation of order 2m.